A method for preparing a c12a7 electron compound nanopowder

CN122940191APending Publication Date: 2026-10-20NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611197528.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

本发明的制备方法不仅克服了现有溶液前驱体辅助高温煅烧法中“溶液过程仅用于前驱体制备、电子注入仍依赖700℃~1550℃高温煅烧、本质上仍为液相前驱体与高温固相还原组合的两步法”的技术局限,更将传统“先高温合成绝缘C12A7:O2-、再高温还原”的两步法范式革新为真正的低温液相一步法,从根本上解决了现有技术因超高温处理导致的能耗巨大、工艺流程繁琐、颗粒严重烧结及比表面积低等技术问题,为电子化合物功能材料的绿色、高效制备提供了全新路径

Benefits of technology

1、本发明提供了一种C12A7电子化合物纳米粉末的制备方法,在有机溶剂存在下,将可溶性钙盐、铝盐和螯合剂混合后进行水解络合反应,形成前驱体溶胶;将碱金属-冠醚络合物溶液与前驱体溶胶混合,并进行溶剂热反应,反应过程中,前驱体溶胶中的钙、铝组分在螯合剂的导向作用下发生水解缩聚反应,结晶并生长形成C12A7的笼状骨架;与此同时,碱金属-冠醚络合物溶液中的溶剂化电子作为液相强还原剂,从液相迁移并进入正在形成的C12A7笼腔中,将C12A7笼中的O2-置换为自由电子,完成电子注入,随后经后处理,得到C12A7电子化合物纳米粉末。其中,溶剂热反应的条件为:于150℃~250℃下反应6h~24h。本发明的制备方法工艺简单、条件温和、易于规模化生产,解决了现有C12A7电子化合物的制备方法普遍存在温度高、能耗大、比表面积低、工艺繁琐的问题,为电子化合物功能材料的绿色、高效制备提供了全新路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of inorganic functional material preparation technology, specifically to a method for preparing C12A7 electronic compound nanopowder. The method includes: in the presence of an organic solvent, mixing a soluble calcium salt, an aluminum salt, and a chelating agent, followed by a hydrolysis-complexation reaction to form a precursor sol; mixing an alkali metal-crown ether complex solution with the precursor sol, and then performing a solvothermal reaction to obtain C12A7 electronic compound nanopowder; wherein the solvothermal reaction conditions are: reaction at 150℃~250℃ for 6h~24h. The preparation method of this invention is simple, has mild conditions, and is easy to scale up for production. It solves the problems of high temperature, high energy consumption, low specific surface area, and cumbersome processes commonly found in existing C12A7 electronic compound preparation methods, providing a new path for the green and efficient preparation of electronic compound functional materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic functional materials preparation technology, specifically to a method for preparing C12A7 electronic compound nanopowder. Background Technology

[0002] C12A7 electron compound (i.e., C12A7:e) - C12A7 is an inorganic electronic compound with electrons as anions, possessing a unique cage-like structure and excellent electronic conductivity. Each unit cell consists of 12 interconnected nanoscale cage-like structures forming a positively charged framework, with free electrons residing within four of these cage-like structures. This endows the material with excellent electrical conductivity and a low work function (approximately 2.4 eV). - It has broad application prospects in fields such as field emission, catalyst support, solid electrolyte, and photoelectric conversion.

[0003] C12A7:e is currently available. - The preparation methods mainly include high-temperature carbothermal reduction, high-temperature aluminothermal reduction, and solution precursor-assisted high-temperature calcination. Among these, the high-temperature carbothermal reduction method primarily employs a process of first synthesizing insulating C12A7:O... 2- The two-step method of "reduction at high temperature". For example, patent CN115044977A discloses a C12A7:e - Electron target material and its preparation method are disclosed. The method uses CaCO3 and Al2O3 as raw materials, synthesizing C12A7 insulators via a solid-state reaction at 1300℃~1400℃. The C12A7 is then placed in a covered graphite container and melted and reduced in a vacuum induction furnace at 1450℃~1550℃, with electron injection achieved through directional solidification. Patent CN115121294A discloses a C12A7:e... - Preparation of electron-emitting compounds, Pd-C12A7:e - Catalyst and its preparation and application: This method uses CaCO3 and Al2O3 as raw materials, and synthesizes C12A7 by heating in a muffle furnace at 1000℃~1450℃ for 6h~10h, and then carbothermally reducing it in a vacuum atmosphere furnace at 1250℃~1500℃ for 2h~4h. Although this method is mature, it has the following defects: (1) Two ultra-high temperature treatments, with the highest temperature reaching 1550℃ and a total time of 8h~14h, result in huge energy consumption and high production costs; (2) The particles are severely sintered at high temperatures, and the specific surface area of ​​the product is usually less than 5m². 2 / g, when used as a catalyst carrier, severely limits the dispersion of active components; (3) The process involves more than 9 unit operations such as ball milling → standing → drying → grinding → high temperature calcination → crushing → grinding → high temperature reduction in carbon crucible → ultrasound, requiring the configuration of various special equipment such as high temperature muffle furnace and vacuum atmosphere furnace, making it difficult to guarantee consistency between batches and making industrial scale-up difficult.

[0004] High-temperature aluminothermic reduction methods, such as those reported in "Facile and Massive Aluminothermic Synthesis of Mayenite Electrides from Cost-Effective Oxide and Metal Precursors," involve mixing CaO, Al2O3, and Al powder, followed by calcination at 1100℃ in a flowing Ar atmosphere for 8 hours to directly obtain C12A7:e. - Powder. Compared with the traditional multi-step method, this scheme simplifies the process flow, but the reaction temperature is still above 1100℃, and the product is micron-sized particles with limited specific surface area, failing to fundamentally solve the problems of high-temperature sintering and low specific surface area.

[0005] Solution precursor-assisted high-temperature calcination method, patent CN105819479A discloses a C12A7:e - A method for preparing electronic compound nanopowders involves using soluble calcium and aluminum salts as raw materials, adding organic solvents and chelating agents to form a sol, drying to obtain precursor powder, and then calcining and reducing it at a high temperature of 700℃~1550℃ to obtain C12A7:e. - Nanopowders. Although this scheme introduces the concept of "solution method", electron injection still relies on high-temperature calcination of 700℃~1550℃. The solution process is only used for precursor preparation. In essence, it is still a two-step method of "liquid phase preparation of precursor + high-temperature solid phase reduction". It does not solve the problems of high energy consumption, complicated process and low specific surface area of ​​product caused by high temperature treatment. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing C12A7 electronic compound nanopowder. Using soluble calcium salts, aluminum salts, chelating agents, and alkali metal-crown ether complexes as raw materials, in the presence of an organic solvent, the soluble calcium salts, aluminum salts, and chelating agents are first mixed and subjected to a hydrolysis-complexation reaction to form a precursor sol. Subsequently, the precursor sol is mixed with an alkali metal-crown ether complex solution and subjected to a solvothermal reaction to obtain C12A7 electronic compound nanopowder. This invention utilizes the strongly reducing solvated electrons (E≈-2.9V) generated by the dissociation of the alkali metal-crown ether complex in an organic solvent as a strong liquid-phase reducing agent, simultaneously achieving the crystallization growth of the C12A7 cage-like framework and in-situ electron injection under solvothermal conditions. The preparation method of this invention not only overcomes the technical limitations of existing solution precursor-assisted high-temperature calcination methods, which state that "the solution process is only used for precursor preparation, electron injection still relies on high-temperature calcination at 700℃~1550℃, and it is essentially still a two-step method combining liquid-phase precursor and high-temperature solid-phase reduction," but also improves upon the traditional method of "first synthesizing insulating C12A7:O at high temperature." 2- The two-step process of “reduction at high temperature” is a true one-step process in low temperature liquid phase, which fundamentally solves the technical problems of huge energy consumption, complicated process flow, severe particle sintering and low specific surface area caused by ultra-high temperature treatment in existing technologies, and provides a new path for the green and efficient preparation of electronic compound functional materials.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The purpose of this invention is to provide a method for preparing C12A7 electronic compound nanopowder, comprising the following steps: S1. In the presence of an organic solvent, soluble calcium salt, aluminum salt and chelating agent are mixed and subjected to a hydrolysis-complexation reaction to form a precursor sol.

[0008] S2. The alkali metal-crown ether complex solution is mixed with the precursor sol and subjected to a solvothermal reaction. During the reaction, the calcium and aluminum components in the precursor sol undergo hydrolysis and condensation under the guidance of the chelating agent, crystallizing and growing to form a cage-like framework of C12A7. Simultaneously, solvated electrons in the alkali metal-crown ether complex solution migrate from the liquid phase into the forming C12A7 cage cavity under the drive of concentration gradient and chemical potential, thereby converting the O in the C12A7 cage into oxygen. 2- The electrons are replaced with free electrons, electron injection is completed, and after post-processing, C12A7 electronic compound nanopowder is obtained; the solvothermal reaction conditions are: reaction at 150℃~250℃ for 6h~24h.

[0009] Preferably, the molar ratio of soluble calcium salt to aluminum salt is 10~12:13~15.

[0010] Preferably, the chelating agent is citric acid, and the ratio of the total molar amount of soluble calcium salt and aluminum salt to the molar amount of the chelating agent is 1:1 to 3.

[0011] Preferably, the soluble calcium salt is Ca(NO3)2·4H2O, and the aluminum salt is Al(NO3)3·9H2O. Ca(NO3)2·4H2O and Al(NO3)3·9H2O have extremely high solubility in water and polar organic solvents, enabling Ca... 2+ With Al 3+ The sol-gel method achieves uniform dispersion at the molecular level and complete complexation with citric acid to form a homogeneous and transparent sol precursor. If poorly soluble raw materials such as calcium oxide, calcium hydroxide, aluminum oxide, or aluminum hydroxide are used, it is impossible to achieve uniform molecular-level mixing in the liquid phase, making it difficult to form a stable sol system. This results in the loss of the core advantages of the sol-gel method in terms of chemical composition uniformity and structural controllability.

[0012] Preferably, the mass ratio of the alkali metal-crown ether complex to the calcium salt is 5~8:1.

[0013] Preferably, the conditions for the hydrolysis-complexation reaction are: stirring at 40℃~80℃ for 1h~3h.

[0014] Preferably, the solvothermal reaction conditions are: reacting at 180℃~220℃ for 12h~16h.

[0015] Preferably, the alkali metal-crown ether complex solution is prepared according to the following steps: Under inert gas protection, alkali metals and crown ethers are co-dissolved in anhydrous tetrahydrofuran to obtain an alkali metal-crown ether complex solution; wherein the molar ratio of alkali metal to crown ether is 0.8~1.2:1. Anhydrous tetrahydrofuran is chosen as the solvent in this invention primarily because it possesses excellent solubility for alkali metal-crown ether complexes, ensuring complete dissociation and release of solvated electrons. Furthermore, tetrahydrofuran is an aprotic polar solvent, and its molecular structure does not contain active hydrogen, effectively preventing protonation side reactions between the solvent and the alkali metal or solvated electrons, thus ensuring the stable existence of solvated electrons and their strong reducing properties. In contrast, protic solvents containing hydroxyl groups, such as ethylene glycol, not only fail to effectively dissolve and stabilize alkali metal-crown ether complexes, but their hydroxyl groups also react directly with the alkali metal, leading to the deactivation of solvated electrons; therefore, they are not suitable for this invention.

[0016] Preferably, the alkali metal is selected from Na or K, and the crown ether is selected from 15-crown ether-5 or 18-crown ether-6.

[0017] Preferably, the post-processing operation is as follows: under inert gas protection, the C12A7 electronic compound nanopowder is washed repeatedly with anhydrous ethanol and deionized water 3 to 5 times, then centrifuged at a speed of 8000 r / min to 12000 r / min to remove unreacted raw materials and by-products; then vacuum dried at 60℃ to 80℃ for 6h to 12h.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a method for preparing C12A7 electronic compound nanopowder. In the presence of an organic solvent, soluble calcium salts, aluminum salts, and a chelating agent are mixed and subjected to a hydrolysis-complexation reaction to form a precursor sol. An alkali metal-crown ether complex solution is then mixed with the precursor sol and subjected to a solvothermal reaction. During the reaction, the calcium and aluminum components in the precursor sol undergo hydrolysis-condensation under the guidance of the chelating agent, crystallizing and growing to form a cage-like framework of C12A7. Simultaneously, the solvated electrons in the alkali metal-crown ether complex solution act as a strong reducing agent in the liquid phase, migrating from the liquid phase and entering the forming C12A7 cage cavity, thereby converting the O in the C12A7 cage into O. 2- Electron injection is performed by replacing electrons with free electrons, followed by post-processing to obtain C12A7 electronic compound nanoparticles. The solvothermal reaction conditions are: reaction at 150℃~250℃ for 6h~24h. The preparation method of this invention is simple, mild, and easy to scale up, solving the problems of high temperature, high energy consumption, low specific surface area, and cumbersome processes commonly found in existing C12A7 electronic compound preparation methods. It provides a new pathway for the green and efficient preparation of electronic compound functional materials.

[0019] Compared to the solution precursor-assisted method that relies on high-temperature calcination and the traditional "high-temperature synthesis of insulating C12A7:O" method... 2- The two-step process of "high-temperature reduction" is the first to couple crystal growth and electron injection into the same liquid phase system, and complete it directly under mild conditions not exceeding 250°C. This completely avoids the problems of huge energy consumption, lengthy process and severe sintering of product particles and significant reduction in specific surface area caused by ultra-high temperature treatment.

[0020] 2. The C12A7 electronic compound nanopowder prepared by this invention has a high specific surface area and abundant surface active sites, showing excellent potential application prospects in the field of catalysis. Attached Figure Description

[0021] Figure 1 The image shows the XRD pattern of the C12A7 electronic compound nanopowder from Example 1.

[0022] Figure 2 This is a SEM image of the C12A7 electronic compound nanopowder from Example 1.

[0023] Figure 3 1.2wt% Ru / C12A7:e - SEM surface scan and EDS elemental distribution map of the catalyst, where a is the SEM surface scan, b is Al, c is Ru, d is Ca, and e is O.

[0024] Figure 4 1.2wt% Ru / C12A7:e - Figure showing the test results of the catalyst's ammonia synthesis catalytic performance.

[0025] Figure 5 The image shows the nitrogen adsorption isotherm curve of the C12A7 electronic compound nanopowder in Example 1. Detailed Implementation

[0026] The technical solution of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0027] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased on the market or prepared by existing methods.

[0028] In existing technologies, the preparation of C12A7 electron compounds mainly employs high-temperature carbothermal reduction, high-temperature aluminothermal reduction, and solution precursor-assisted high-temperature calcination. Among these, the high-temperature carbothermal reduction method uses CaCO3 and Al2O3 as raw materials. After synthesizing C12A7 insulators through a high-temperature solid-state reaction at 1000℃~1450℃, a carbothermal reduction is then performed at 1250℃~1550℃ to inject electrons. The highest processing temperature reaches 1550℃, and the total processing time is as long as 8h~14h. This method not only consumes a huge amount of energy but also leads to severe particle sintering, with the product's specific surface area typically below 5m². 2 / g, the process involves more than 9 unit operations, making industrial scale-up difficult; although the high-temperature aluminothermic reduction method simplifies the process, the reaction temperature is still around 1100℃, and the product is micron-sized particles with limited specific surface area; although the solution precursor-assisted high-temperature calcination method introduces solution-based preparation of precursors, electron injection still relies on high-temperature calcination of 700℃~1550℃, which is essentially still a two-step method of "liquid-phase precursor preparation + high-temperature solid-phase reduction", and does not fundamentally solve the problems of high energy consumption, complicated process and low specific surface area of ​​product caused by high-temperature treatment.

[0029] To address the problems existing in the prior art, this invention provides a method for preparing C12A7 electronic compound nanopowder, comprising the following steps: In the presence of an organic solvent, a soluble calcium salt, an aluminum salt, and a chelating agent are mixed and subjected to a hydrolysis-complexation reaction to form a precursor sol; wherein the molar ratio of the soluble calcium salt to the aluminum salt is 12:14; an alkali metal-crown ether complex solution is mixed with the precursor sol and subjected to a solvothermal reaction; during the reaction, the calcium and aluminum components in the precursor sol undergo hydrolysis-condensation reaction under the guidance of the chelating agent, crystallizing and growing to form a cage-like framework of C12A7; simultaneously, the solvated electrons in the alkali metal-crown ether complex solution act as a strong reducing agent in the liquid phase, migrating from the liquid phase and entering the forming C12A7 cage cavity, thereby converting the O in the C12A7 cage into a strong reducing agent. 2- The electrons are replaced with free electrons, and after post-processing, C12A7 electronic compound nanopowder is obtained.

[0030] This invention replaces traditional carbothermic / aluminothermic reducing agents with strongly reducing solvated electrons generated by an alkali metal-crown ether complex reduction system. Under solvothermal conditions, it simultaneously achieves the crystal growth and in-situ electron injection of the C12A7 cage structure. This not only overcomes the technical limitations of existing solution precursor-assisted high-temperature calcination methods, where "the solution process is only used for precursor preparation, electron injection still relies on high-temperature calcination at 700℃~1550℃, and it is essentially still a two-step method combining liquid-phase precursor and high-temperature solid-phase reduction," but also improves upon the traditional method of "first synthesizing insulating C12A7:O at high temperature." 2- The two-step process of "high-temperature reduction" has been transformed into a true one-step process in low-temperature liquid phase, which fundamentally solves the technical problems of huge energy consumption, complicated process flow, severe particle sintering and low specific surface area caused by ultra-high temperature treatment (>1250℃) in the existing technology. It realizes the direct preparation of C12A7 electronic compound nanopowder with high specific surface area and high catalytic activity under low temperature conditions of ≤250℃.

[0031] In the solvothermal system of this invention, the solvated electrons generated by the dissociation of the alkali metal-crown ether complex have extremely strong reducing properties (E≈-2.9V vs SHE), and their chemical potential is much lower than that of the O in the C12A7 cage. 2- The stability region of O within the C12A7 cage. In this strongly reducing liquid environment, the O... 2- Thermodynamically unstable, it will inevitably be reduced to free electrons; simultaneously, the solvothermal reaction temperature (150℃~250℃) is sufficient to drive the calcium-aluminum component to crystallize and form a C12A7 framework, but is far below O 2- The temperature threshold for re-stabilization. Therefore, this invention achieves in-situ electron injection simultaneously with the formation of the C12A7 cage-like framework, directly generating C12A7:e - Instead of first forming C12A7:O 2-The oxides are then reduced a second time.

[0032] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the following will provide a detailed description in conjunction with specific embodiments: Example 1 A method for preparing C12A7 electronic compound nanopowder includes the following steps: S1. Dissolve 1.42 g of Ca(NO3)2·4H2O and 2.63 g of Al(NO3)3·9H2O in 10 mL of anhydrous THF, then add 4.99 g of citric acid and stir at 60 °C for 2 h to form a uniform and transparent precursor sol; wherein, Ca 2+ With Al 3+ The molar ratio is 12:14, and the ratio of the total molar amount of Ca(NO3)2·4H2O and Al(NO3)3·9H2O to the molar amount of citric acid is 1:2.

[0033] S2. Under Ar atmosphere protection, 0.72 g of metallic sodium and 8.25 g of 18-crown-6 were dissolved in 4 mL of anhydrous THF at a molar ratio of 1:1. The mixture was stirred at room temperature until completely dissolved to form a deep blue sodium-crown ether complex solution, i.e., an alkali metal-crown ether complex solution. The alkali metal-crown ether complex solution was added to the above precursor sol and mixed. After stirring evenly, the mixture was transferred to a high-pressure reactor (70% filling) and subjected to a solvothermal reaction at 200 °C for 14 h. After the reaction was completed, the mixture was naturally cooled to room temperature. Subsequently, under Ar atmosphere protection, the mixture was washed four times with anhydrous ethanol and deionized water, centrifuged at 10000 r / min for 5 min, and then vacuum dried at 70 °C for 8 h to obtain C12A7 electronic compound nanopowder.

[0034] The resulting product is a black powder, which reacts with C12A7:O 2- The white appearance of the insulator is significantly different and conforms to the typical appearance characteristics of C12A7 electronic compounds known in the art.

[0035] like Figure 1As shown, the diffraction peak positions of the C12A7 electron compound nanopowder in Example 1 of this invention are highly consistent with the standard C12A7 spectrum, and no impurity phase diffraction peaks were observed. This proves that the present invention can achieve the controllable preparation of pure-phase C12A7 electron compounds under low-temperature solvothermal conditions of 200℃, and the product has good crystallinity. In addition, the diffraction peak positions of the C12A7 electron compound nanopowder in Example 1 of this invention are highly consistent with the crystal structure data of C12A7 electron compounds reported in the literature (Palacios, L.; De La Torre, Á. G.; Bruque, S.; et al. Inorg. Chem. 2007, 46, 4167-4176.), which preliminarily indicates that free electrons have been formed within the product cage.

[0036] like Figure 2 As shown, the C12A7 electronic compound nanopowder of Example 1 of this invention exhibits a nanoscale particle morphology, without the severe sintering and large-scale agglomeration phenomena caused by ultra-high temperature treatment in traditional high-temperature solid-state methods. The particles are generally at the nanoscale. This result indicates that the low-temperature solvothermal method of this invention effectively avoids ultra-high temperature treatment, inhibits particle sintering and growth, and preserves the nanoscale effect. This not only meets the design goal of "nanopowder" but also lays the morphological foundation for the high specific surface area of ​​the material.

[0037] like Figure 3 As shown, Ca, Al, and O, the main elements of the C12A7 framework, are highly uniformly distributed within the test area, with no phase separation or local enrichment observed; the active metal Ru also exhibits a uniform distribution throughout the entire area, without obvious agglomeration. These results verify that the C12A7 electronic compound nanopowder carrier has uniform components, and that the Ru active component has good dispersibility on the carrier surface.

[0038] like Figure 5 As shown, the N2 adsorption-desorption isotherm and BET test results of the C12A7 electronic compound nanopowder in Example 1 of this invention show that its specific surface area (BET) is 9.56 m². 2 / g. Compared to C12A7:e prepared by the traditional high-temperature carbothermic / aluminothermic reduction method. - (Specific surface area is usually less than 5m²) 2 / g), the present invention uses a low-temperature liquid phase one-step method to increase the specific surface area of ​​the pure support by nearly 1 times, effectively avoiding particle sintering and specific surface area loss caused by ultra-high temperature treatment, providing more abundant surface anchoring points for the active components of the catalyst, and better adapting to the application requirements of the catalyst support.

[0039] Example 2 A method for preparing C12A7 electronic compound nanopowder is the same as the method in Example 1, except that the ratio of the total molar amount of Ca(NO3)2·4H2O and Al(NO3)3·9H2O to the molar amount of citric acid in S1 is replaced from 1:2 to 1:1, thus obtaining C12A7 electronic compound nanopowder.

[0040] Example 3 A method for preparing C12A7 electronic compound nanopowder is the same as the preparation method in Example 1, except that the ratio of the total molar amount of Ca(NO3)2·4H2O and Al(NO3)3·9H2O to the molar amount of citric acid in S1 is replaced from 1:2 to 1:3, thus obtaining C12A7 electronic compound nanopowder.

[0041] Example 4 A method for preparing C12A7 electronic compound nanopowder is the same as the preparation method in Example 1, except that the sodium metal in S2 is replaced with potassium metal to obtain C12A7 electronic compound nanopowder.

[0042] Example 5 A method for preparing C12A7 electronic compound nanopowder is the same as the preparation method in Example 1, except that the vacuum drying at 70°C for 8 hours in step S2 is replaced with vacuum drying at 60°C for 12 hours to obtain C12A7 electronic compound nanopowder.

[0043] Example 6 A method for preparing C12A7 electronic compound nanopowder is the same as the preparation method in Example 1, except that the vacuum drying at 70°C for 8 hours in step S2 is replaced with vacuum drying at 80°C for 6 hours to obtain C12A7 electronic compound nanopowder.

[0044] Example 7 A method for preparing C12A7 electronic compound nanopowder is the same as that in Example 1, except that the molar ratio of Ca(NO3)2·4H2O to Al(NO3)3·9H2O in S1 is replaced by 10:13 instead of 12:14, thus obtaining C12A7 electronic compound nanopowder.

[0045] Example 8 A method for preparing C12A7 electronic compound nanopowder is the same as that in Example 1, except that the molar ratio of Ca(NO3)2·4H2O to Al(NO3)3·9H2O in S1 is replaced by 12:15 instead of 12:14, thus obtaining C12A7 electronic compound nanopowder.

[0046] application: To further verify the catalytic performance of the C12A7 electron compound nanopowder of the present invention, the C12A7 electron compound nanopowder prepared in Example 1 was used as a support, and ruthenium (Ru) active component was loaded by a solventless thermal decomposition method to prepare Ru / C12A7:e - The catalyst was used for performance evaluation in ammonia synthesis.

[0047] Specific preparation process: using dodecacarbonylruthenium (Ru3(CO)) 12 Using ruthenium as the source, in an inert atmosphere glove box (water and oxygen content <0.1ppm), C12A7 electron compound nanopowder was mixed with Ru3(CO). 12 Weigh and mix according to the target loading of 1.2 wt% (approximately 0.031 g of Ru3(CO) is weighed out for every 1.0 g of C12A7 electronic compound nanopowder). 12 The mixture was then placed in an agate mortar and ground thoroughly for 15 minutes until homogeneous. The mixture was then transferred to a quartz tube and ground under a vacuum of 10... -2 Under the condition of Pa, the quartz tube was fused and sealed; the sealed quartz tube was then placed in a muffle furnace for programmed temperature heat treatment: the temperature was increased to 40℃ at a rate of 2℃ / min and held for 1 hour; then increased to 70℃ at a rate of 0.25℃ / min and held for 1 hour; then increased to 120℃ at a rate of 0.4℃ / min and held for 1 hour; finally, increased to 250℃ at a rate of 0.9℃ / min and held for 2 hours. After the heat treatment, the quartz tube was allowed to cool naturally to room temperature with the furnace. During this process, Ru3(CO) 12 Through stepwise thermal decomposition, metallic Ru nanoparticles are formed and uniformly deposited on the surface of C12A7 electron compound nanoparticle carrier, yielding Ru / C12A7:e - Catalyst, denoted as 1.2 wt% Ru / C12A7:e - Catalyst. The resulting Ru / C12A7:e - The catalyst was removed from the glove box, ground, sealed, and stored for later use.

[0048] Performance testing method: Catalytic performance testing was conducted in a fixed-bed continuous flow reactor. The specific procedure was as follows: 0.2 g of 1.2 wt% Ru / C12A7:e was added... - The catalyst is packed in a stainless steel reaction tube with an inner diameter of 8 mm. The catalyst bed height is about 4 mm, and both ends are fixed with quartz wool.

[0049] Before testing, add 1.2wt% Ru / C12A7:e -The catalyst was first activated in situ by H2 / N2 mixed gas (H2 to N2 volume ratio 3:1, purity >99.99995%) at 0.1 MPa pressure: the total flow rate of the mixed gas was controlled at 60 mL / min (corresponding to a space velocity of approximately 18000 mL·g⁻¹). -1 ·h -1 The temperature of the reaction tube was raised to 400°C within 2 hours using a programmed temperature ramp method and then maintained at that temperature for 1 hour.

[0050] The ammonia synthesis reaction was carried out at two pressures: 0.1 MPa (atmospheric pressure) and 1.0 MPa, with the composition and flow rate of the feed gas remaining consistent with those in the reduction and activation stages. After the reaction reached steady state, the outlet gas was passed into an absorption bottle containing a 5 mmol / L sulfuric acid solution, allowing the generated ammonia to be fully absorbed and converted into NH4. + NH4 was analyzed using an ion chromatograph equipped with a conductivity detector. + Quantitative analysis was performed, and the ammonia production was calculated using the external standard method.

[0051] The ammonia synthesis rate is expressed as the amount of ammonia produced per unit mass of catalyst per unit time, in μmol·g⁻¹. -1 ·h -1 The volume fraction of ammonia at the outlet is determined by the ratio of the actual ammonia production to the theoretical thermodynamic equilibrium concentration.

[0052] Depend on Figure 4 It was found that, under conditions of 400℃ and 0.1MPa, the 1.2wt% Ru / C12A7:e prepared by this invention... - The ammonia synthesis rate of the catalyst is 2320 μmol·g cat -1 ·h -1 When the reaction pressure was increased to 1.0 MPa, the ammonia synthesis rate increased to 8145 μmol·g. cat -1 ·h -1 The above catalytic activity is similar to that in the literature (Ru-Loaded C12A7:e - The performance level of the Ru / C12A7 electron compound catalyst reported in "Electride as a Catalyst for Ammonia Synthesis" is comparable to that of the C12A7:e catalyst prepared in the next step at a low temperature of ≤250℃ in this invention is comparable to that of the catalyst reported in "Electride as a Catalyst for Ammonia Synthesis". - The support has good electron supply capability, and the Ru catalyst supported on it exhibits excellent catalytic activity in the ammonia synthesis reaction.

[0053] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

Claims

1. A method for preparing C12A7 electronic compound nanopowder, characterized in that, Includes the following steps: In the presence of an organic solvent, soluble calcium salts, aluminum salts and chelating agents are mixed and subjected to a hydrolysis-complexation reaction to form a precursor sol. An alkali metal-crown ether complex solution was mixed with a precursor sol and subjected to a solvothermal reaction. During the reaction, the calcium and aluminum components in the precursor sol underwent hydrolysis and condensation under the guidance of a chelating agent, crystallizing and growing to form a cage-like framework of C12A7. Simultaneously, solvated electrons in the alkali metal-crown ether complex solution migrated from the liquid phase and entered the forming C12A7 cage cavity, releasing the oxygen in the C12A7 cage. 2- The electrons are replaced with free electrons, and after post-processing, C12A7 electronic compound nanopowder is obtained; The solvothermal reaction conditions are: reaction at 150℃~250℃ for 6h~24h.

2. The preparation method according to claim 1, characterized in that, The molar ratio of soluble calcium salt to aluminum salt is 10~12:13~15.

3. The preparation method according to claim 1, characterized in that, The soluble calcium salt is Ca(NO3)2·4H2O, and the aluminum salt is Al(NO3)3·9H2O.

4. The preparation method according to claim 1, characterized in that, The chelating agent is citric acid, and the ratio of the total molar amount of soluble calcium salt and aluminum salt to the molar amount of the chelating agent is 1:1~3.

5. The preparation method according to claim 1, characterized in that, The mass ratio of alkali metal-crown ether complex to calcium salt is 5~8:

1.

6. The preparation method according to claim 1, characterized in that, The conditions for the hydrolysis-complexation reaction are: stirring at 40℃~80℃ for 1h~3h.

7. The preparation method according to claim 1, characterized in that, Alkali metal-crown ether complex solutions are prepared according to the following steps: Under inert gas protection, alkali metals and crown ethers are dissolved together in anhydrous tetrahydrofuran to obtain an alkali metal-crown ether complex solution; wherein the molar ratio of alkali metal to crown ether is 0.8~1.2:

1.

8. The preparation method according to claim 7, characterized in that, The alkali metal is selected from Na or K, and the crown ether is selected from 15-crown ether-5 or 18-crown ether-6.

9. The preparation method according to claim 1, characterized in that, The post-processing steps are as follows: Under inert gas protection, C12A7 electronic compound nanopowder was washed repeatedly with anhydrous ethanol and deionized water 3 to 5 times, then centrifuged and dried under vacuum at 60℃ to 80℃ for 6 to 12 hours.

Citation Information

Patent Citations

  • Preparation method of C12A7:e&lt;-&gt; electronic compound nano powder

    CN105819479A

  • Preparation of C12A7: e &lt;-&gt; electron compound, Pd-C12A7: e &lt;-&gt; catalyst, and preparation and application of Pd-C12A7: e &lt;-&gt; catalyst

    CN115121294A